A hybrid strategy combining minimized leading-edge electric-heating and superhydro-/ice-phobic surface coating for wind turbine icing mitigation. (September 2019) - Gao, Linyue; Liu, Yang; Ma, Liqun; Hu, Hui
Abstract: A hybrid anti-icing strategy that combines minimized electro-heating at the blade leading edge and a superhydro-/ice-phobic coating to cover the blade surface was explored for wind turbine icing mitigation. The experimental study was conducted in an Icing Research Tunnel available at Iowa State University (ISU-IRT) with a turbine blade model with DU91-W2-250 airfoil in the model cross-section exposed under different icing conditions. While a superhydro-/ice-phobic surface coating was used to cover the entire blade surface, a strip of electric heating film was used to wrap around the leading edge of the blade model. By using the superhydro-/ice-phobic coating to cover the entire blade surface, the hybrid strategy with the electric heating element covering only 5%–10% of the blade front surface would be able to keep the entire blade surface ice free under both rime and glaze icing conditions. In comparison to the conventional strategy to brutally heating the entire hydrophilic blade surface to keep the blade ice free, the hybrid strategy was found to be able to achieve the same anti-/de-icing performance with substantially less power consumption (i.e., up to ∼90% saving in the required power consumption), making it a very promising strategy for wind turbine icing mitigation. Highlights: A hybrid strategy combining heating and superhydrophic surface was proposed. The properties of superhydrophic surface and hydrophilic surface were quantified. The anti-icing performance of various strategies over a turbine blade was evaluated. The leading-edge heating element was minimized to 5%–10% of the chord length. The hybrid strategy can prevent ice accretion with 10% of the energy requirement.